Gender Inequality in Various Personal Laws in India with Special Reference to North-East - Pradeep Kumar,; Baba Nyicor, (AG Volumes, 2026)
Personal laws in India are always touching upon the complex issue of gender inequality. India being a secular state, religion and personal laws are basically interlinked where the moral, ethical, cultural, and religious beliefs of people differ from one another. To impart justice different people, have their different sets of laws. The position of women in the present era is reputable but neither equal nor higher to the male counterpart, it is still shadowed by patriarchal society and the various customs associated with day-to-day life. With changes in the present social system, corresponding changes in the legal system are increasingly felt necessary. However, the societal changes itself have not taken place evenly in the same geographically defined areas or remains uneven among the different sections of society. The present chapter will attempt to provide an exposition of gender inequality in various personal laws in India with special reference to North-East India, which is a profoundly problematic narrative that needs to be reimagined and interrogated.